The Role of Ecotourism in Improving the Economic and Environmental Welfare of Local Communities in Bali - Mulyana, Hadi (Westscience Press, 2025)
This study investigates the role of ecotourism in enhancing the economic and environmental welfare of local communities in Bali. Using a quantitative research design, data were collected from 150 respondents actively engaged in ecotourism activities through a structured questionnaire with a Likert scale (1–5). The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS 3) to test the hypothesized relationships. The results show that ecotourism has a positive and significant effect on economic welfare, reflected in increased income, job opportunities, and local business growth. Similarly, ecotourism significantly improves environmental welfare by encouraging conservation practices, sustainable resource management, and environmental awareness. The model explains 26.2% of the variance in economic welfare and 23.6% in environmental welfare, indicating moderate explanatory power. These findings highlight that ecotourism, when integrated with community participation and cultural traditions, can serve as a strategic tool for sustainable development in Bali. This research provides valuable implications for policymakers, tourism stakeholders, and local communities to strengthen ecotourism initiatives that balance economic growth with ecological preservation.